Analisis hukum terhadap dasar pertimbangan hakim dalam menjatuhkan putusan perkara tindak pidana narkotika (Studi kasus Putusan Pengadilan Negeri Karawang Nomor 325/Pid.Sus/2022/PN Kwg) - Adinda Rizki Nursanda; Nia Ayu Mayang Sari (LPPM Iblam School of Law, 2026)
Drug abuse is a complex problem involving social, health, and legal dimensions that poses serious challenges to individuals and society. This study aims to analyze the legal considerations of judges in deciding narcotics cases in the Decision of the Karawang District Court Number 325/Pid.Sus/2022/PN Kwg and to examine the preventive and protective measures implemented to address drug abuse in Karawang Regency. This research employs a normative juridical method with statutory and case approaches, analyzed descriptively. The results show that the defendant, Jemi Permadi alias Jemi bin Hasim, was legally and convincingly proven guilty of acting as an intermediary in the illegal sale and purchase of Class I narcotics (methamphetamine) as stipulated in Article 114 paragraph (1) of Law Number 35 of 2009 concerning Narcotics. Based on the facts revealed during the trial, the panel of judges concluded that all elements of the criminal offense had been fulfilled and that no justifying or excusing circumstances were found. Therefore, the defendant was sentenced to seven years of imprisonment and fined IDR 1,000,000,000, with a subsidiary penalty of six months imprisonment if the fine is not paid. In addition to law enforcement efforts, the Karawang Regency Government has demonstrated a strong commitment to preventing and combating drug abuse through preventive, repressive, and rehabilitative measures. This commitment is reflected in the cooperation with the Karawang Regency National Narcotics Agency (BNNK) and the implementation of Regional Regulation Number 9 of 2019, which emphasizes the importance of medical and social rehabilitation for drug addicts. These initiatives align with the principles of Law Number 35 of 2009, which recognizes drug addicts as individuals who require rehabilitation to support their recovery and social reintegration.